Colonic adenocarcinoma revealing Crohn's disease: a case report - Ankouz, Amal (BioMed Central, 2010)
INTRODUCTION: There is growing evidence from epidemiological studies and clinicopathological data obtained from case reports that Crohn's disease is associated with an increased risk of carcinoma of the large bowel. CASE PRESENTATION: A 70-year-old Arabic African man with undiagnosed Crohn's disease presented with acute abdominal obstruction due to an occlusive carcinoma of the sigmoid. At laparotomy, the colonic tumor was excised with continuity restored by end-to-end anastomosis. CONCLUSION: The risk of colonic carcinoma in Crohn's disease is increasing. Several case reports actually support the possibility that a genuine association between these two conditions exists.